(untitled) (The Journal of Plant Protection Sciences, 2023)
Tea mosquito bug, Helopeltis theivora Water house (Hemiptera: Miridae) is one of the most serious pests of tea in Bangladesh. It is also widely distributed in India, Sri Lanka, Viet nam, Indonesia, Malaysia and Africa. It is also a phytophagous pest of coffee, cocoa, cashew etc. A group of genomes are treated as a mosquito bug. This bug bears no relation to mosquito and the name ‘Tea Mosquito Bug’ is simply a misnomer. It is considered as one of the major pests of Bangladesh tea because it attacks only to the young shoots that are the actual crop of tea. Ahmed (2) reported that 10 -15% of tea crop is lost annually by Helopeltis which sometimes may go up to 100% crop loss. Both the nymphs and adults damage the plant by sucking sap from young leaves, buds and tender stems. Due to intensive feeding by nymphs and adults, leaves curl up and are badly deformed. In addition to direct crop loss, damage by Helopeltis leads to debilita tion of bushes resulting in die-back with crows-feet and delayed or meager flushing thereafter consequently almost the entire crop is lost. Mamun (6) described that many differ ent tactics are used in IPM strategy for tea mosquito bug in tea plantation, including cul tural practices, biological control agents, pest resistant varieties, physical barriers and chemical pesticides etc. Yet chemical insecti cides have remained as the most powerful tools for controlling this pest in Bangladesh. From the above point of view, efforts were made to evaluate the relative efficacy and eco nomic analysis of some insecticides to find out suitable substitute for efficient control of tea mosquito bug in Bangladesh tea.